2017
DOI: 10.3389/fphys.2017.00417
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Tendon Adaptation in Adolescence: Elite Volleyball Athletes Compared to Untrained Boys and Girls

Abstract: Though the plasticity of human tendons is well explored in adults, it is still unknown how superimposed mechanical loading by means of athletic training affects the properties of tendons during maturation. Due to the increased responsiveness of muscle to mechanical loading, adolescence is an important phase to investigate the effects of training on the mechanical properties of tendons. Hence, in the present study we compared vastus lateralis (VL) architecture, muscle strength of the knee extensor muscles and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 98 publications
5
43
0
3
Order By: Relevance
“…Young’s modulus (GPa) of the free Achilles tendon was calculated by obtaining the slope of the line fitted to the linear region of the tendon stress-strain curve measured at 25, 50, and 70% active muscle contraction conditions. Length normalised mechanical stiffness (kN/strain) was calculated as the product of free Achilles tendon mechanical stiffness and resting length ( Mersmann et al, 2017 ). Free Achilles tendon length calculated from freehand 3DUS data during resting scan was used as a reference measure in deformation and strain calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Young’s modulus (GPa) of the free Achilles tendon was calculated by obtaining the slope of the line fitted to the linear region of the tendon stress-strain curve measured at 25, 50, and 70% active muscle contraction conditions. Length normalised mechanical stiffness (kN/strain) was calculated as the product of free Achilles tendon mechanical stiffness and resting length ( Mersmann et al, 2017 ). Free Achilles tendon length calculated from freehand 3DUS data during resting scan was used as a reference measure in deformation and strain calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, tendon strain during maximum contractions was not only increased chronically in comparison to controls, but also demonstrated significantly greater fluctuations during the period of investigation (Figure 2 ). In addition to the discordant changes of muscle strength and tendon stiffness that occur during a training process, results of a very recent study indicate that also the adaptive potential, at least in response to predominantly plyometric long-term loading, is lower with regard to tendon stiffness compared to muscle strength in both adolescent boys and girls (Mersmann et al, 2017b ). Though from this study it still remains an assumption that maturation contributed to the development musculotendinous imbalance in addition to the unfavorable type of loading, the increased stress and strain observed in the earlier study (Mersmann et al, 2014 ) in adolescent athletes compared to the adults, which were habitually subjected to intense plyometric loading as well, carefully suggest that the risk might be increased during adolescence.…”
Section: Influential Factors Of Imbalanced Muscle-tendon Adaptation Amentioning
confidence: 99%
“…However, the interplay of mechanical loading and changes of the hormonal milieu on muscle and tendon plasticity in general, and with regard to adolescence in particular, is still largely unknown. Similarly, though recent evidence demonstrated that an imbalanced musculotendinous adaptation can occur during adolescence (Mersmann et al, 2014 , 2016 , 2017a , b ), it is yet unclear how the likelihood of an imbalanced adaptation develops as a function of maturation and how it relates to specific types of loading.…”
Section: Influential Factors Of Imbalanced Muscle-tendon Adaptation Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, there seems to be a disproportionate adaptation to athletic training, leading to a lower ratio of tendon to muscle CSA in athletes. This imbalance might contribute to the mismatch of muscle strength and tendon stiffness that has been reported earlier (Mersmann et al, 2017c;Charcharis et al, 2019), with potential implications for the risk of tendon injury (Simpson et al, 2016;Mersmann et al, 2019). Future research might clarify if mid-to late-adolescence is a period of pronounced tendon plasticity and if tendon adaptation can be promoted earlier during maturation by means of specific interventions.…”
Section: A B Cmentioning
confidence: 98%